Henri Lefebvre’s Spatial Theory as Methodology – A Methodological Reconsideration of the Spatial Triad - Vaide, Johan (Journal of Urban Culture Research, 2023)
This article presents a methodological toolset for qualitative socio-spatial analyses based on sociologist Henri Lefebvre’s spatial theory (Lefebvre, 1991). While Lefebvre has been extensively treated as an urban theorist, his work has not been widely explored from a methodological perspective. In the article, Lefebvre’s spatial triad is particularly used to develop a concrete methodology for qualitative socio-spatial analyses. While simultaneously focusing on general methodological aspects, this article draws on how the author applied Lefebvre’s spatial theory in a sociological study about intercultural engagements in Shanghai in the context of China’s opening up reforms. More specifically, Lefebvre’s spatial triad is discussed in relation to a bodily engaged research practice, ethnography and four theory of social science approaches.